If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 6x + -8 = 3x + 7 Reorder the terms: -8 + -1x + 6x = 3x + 7 Combine like terms: -1x + 6x = 5x -8 + 5x = 3x + 7 Reorder the terms: -8 + 5x = 7 + 3x Solving -8 + 5x = 7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + 5x + -3x = 7 + 3x + -3x Combine like terms: 5x + -3x = 2x -8 + 2x = 7 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + 2x = 7 + 0 -8 + 2x = 7 Add '8' to each side of the equation. -8 + 8 + 2x = 7 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 7 + 8 2x = 7 + 8 Combine like terms: 7 + 8 = 15 2x = 15 Divide each side by '2'. x = 7.5 Simplifying x = 7.5
| 40-x^2=o | | 4t+3d=9 | | 8x-11=-9 | | 18x^2-(3x-2)(6x-1)=-17 | | F(X)=x^2-48 | | 4=2a-6 | | s=-1s | | (x+1)[2x+1]=x+0.5(1)+1.000000001 | | (x+1)[2x+1]=x+0.5(1) | | (x+1)[2x+1]=x+0.5 | | (x+1)[2x+1]=x+0.25 | | (9-6i)*m=9-6i | | (x+1)[2x+1]=x | | (9-6i)*m=m | | m=6/m | | x=0x | | 60=x-134 | | 8x^2-35x-38=0 | | (2x+3)(2x+3)+2x-3(2x-3)=(4x+6) | | 3(2x+8)=5(4x-6) | | Log(13)+log(15)=log | | ln(x+4)=1 | | 6*7-2=x | | 0.75(4x-1)=0.25(6x-1) | | 9-5(n+6)=32 | | 42-m=2m-3 | | D^4+5d^3+6D^2-4D-8=0 | | (D^4+5d^3+6D^2-4D-8)y=0 | | 4cosx^4-cosx^2+1=0 | | 5(4+x)-1=2(x+10)-4x | | 4x=120-2x | | 3x+2x=160 |